Superficial surgical site infections following stone and non-stone bile duct surgery- A comparative analysis (Northern International Medical College Journal, 2021)
Background : Superficial surgical site infection (SSSI) is a vital issue after biliary surgery. Surgical site infections remain a major cause of illness in the post-operative period.Objectives : The purpose of the present study was to compare the number of wound infection and the causative organism of surgical site infection of patient of stone and non-stone bile duct surgery.Methodology : This cross-sectional study was carried out in the Department of Surgery at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from May 2017 to April 2018 for a period of 12 months. Patients presented with biliary disease of stone and non-stone variety were selected as study population. Patients were divided into 2 groups designated as group A and group B. Patients with the biliary stone disease were enrolled in group A and the biliary nonstone disease patients were in the group B. Patients were followed up in the postoperative period up to 2 weeks to find out the incidence of wound infection and its risk factors, causative agents, and some other variables. Certain variables were closely monitored to find the postoperative outcome as these variables were standard parameters in assessment of the outcome of the study.Results : A total number of 50 patients were recruited for this study of which 25 patients were enrolled in group A and the 25 patients were enrolled in group B. Mean age was 42.48 ± 17.21 years in group A and 40.04 ± 21.37 years in group B. The difference was not statistically significant ( p=0.659). Males were predominant in both groups. Male female ratio was 1.77:1 and 1.08:1 in group A and group B respectively. Inflammatory evidence of gall bladder with pericholecystic collection was found in 5 (20%) and 6 (24%) patients in group A and group B. There was evidence of cholangitis in 8 (32%) and 4 (16%) patients in group A and group B respectively. Evidence of inflammation at the wound site, was found in 14 (56%) patients in group A and 7 (28%) patients in group B. There was statistically significant difference between these 2 groups in the incidence of superficial surgical site infection, ( p value is 0.045). Regarding per operative collected bile, we found E. Coli in 4 cases in group A and 3 cases in group B ( p value is 0.408). Klebsiella spp. was found in 1 patient in group A. Wound swab C/S identified E. Coli in 1 patient in group A. Staph aureus was found in 1 and 2 patients in group A and group B respectively ( p value is nonsignificant).Conclusion : In conclusion, there is a difference in the incidence of occurrence of surgical site infection and causative agents after stone and non-stone bile duct surgery. Stone disease has increased chance of wound infection than nonstone disease of bile ducts.Northern International Medical College Journal Vol.11 (2) Jan 2020: 458-462